1988
DOI: 10.1017/s0265051700006306
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment in the Assessment of Composition

Abstract: This article describes an experiment in the assessment of composition by group consensus. It was designed to prove that small groups of assessors confronted with only aural evidence of particular compositions could, when using suitable criteria, under certain working conditions, come to similar enough judgements on these compositions to prove the method reliable. The method itself was based on the sessions in assessment held at the University of York in 1977 under the chairmanship of Robert Bunting, but, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Many issues arise here and one of the first is the potential for different assessments by staff. Boud (1995: 99) argues that it is 'quite common for different tutors to give the same piece of work widely different assessments', a view also supported by Brew (1999), Falchikov (1986), Simmonds (1988) and Weaver & Cotrell (1986). At the same time, Brew (1999: 161) states that, provided that criteria are in place and are clear, student and staff marks 'tend to be similar'.…”
Section: A N O V E R V I E W O F T H E L I T E R a T U R Ementioning
confidence: 96%
“…Many issues arise here and one of the first is the potential for different assessments by staff. Boud (1995: 99) argues that it is 'quite common for different tutors to give the same piece of work widely different assessments', a view also supported by Brew (1999), Falchikov (1986), Simmonds (1988) and Weaver & Cotrell (1986). At the same time, Brew (1999: 161) states that, provided that criteria are in place and are clear, student and staff marks 'tend to be similar'.…”
Section: A N O V E R V I E W O F T H E L I T E R a T U R Ementioning
confidence: 96%
“…Even this apparently ideal situation is not without its problems. As the study by Simmonds (1988) shows, even when a number of groups of experienced music teachers/lecturers assessed a small number of pupils' compositions, there were Downloaded by [Umeå University Library] at 17:30 04 April 2015 considerable difficulties in achieving a consensus between the different groups, as well as within each group.…”
Section: Peer Assessment In Composition 1994-95mentioning
confidence: 99%
“…Few actually believe that the ratings can be standardized after the moderation meetings. Indeed, Simmonds's (1988) experiment in the assessment of composition found that there were great flaws in the reliability of group consensus. Using general probability theory, multifaceted Rasch models can estimate and calibrate rater severity and provide a probability-based adjustment to the raw ratings by raters.…”
Section: Using Rasch Models To Calibrate the Assessment Resultsmentioning
confidence: 99%
“…Over the years, studies on assessing compositions in schools and responding to students' compositions have provided different perspectives in assessing compositions (e.g., Burnard, 2002;Feldhusen & Goh, 1995;Freed-Garrod, 1999a, 1999bGreen, 2000;Harris & Hawksley, 1989;Hickey, 2001Hickey, , 2002Mellor, 1999;Plucker & Runco, 1998;Reese, 2003;Salaman, 1988;Simmonds, 1988;Spruce, 2001Spruce, , 2002Stephen, 2003;Swanwick, 1998;Webster, 1987aWebster, , 1987bWebster, , 1987c1989;Webster & Hickey, 1996;Younker, 2003). In this study, an assessment framework (Table 1) is developed with reference to a number of studies on the assessment of compositions.…”
Section: Establishment Of a Music Composition Assessment Frameworkmentioning
confidence: 99%